Plantas invasoras em sistemas agroflorestais com cupuaçuzeiro no município de Presidente Figueiredo (Amazonas, Brasil) - Sousa, Gladys Ferreira de; Oliveira, Luiz Antonio de; Silva, José Ferreira da (Acta Amazonica, 2003)
The increase of weed infestation on agricultural systems cause damages to the crops, decreasing plant productivity by the direct competition or by alelopathy. This work have undertaken a survey and phytosociological analysis of some aspects of weed species that occur in agroforestry systems with cupuassu. The treatments consisted of three crops arrangements (cassava+fruit trees; annuals crops+fruit trees; passion fruit+fruit trees), and three fertilizer management (NPK+OM, with Phosphorus and Phosphorus+leguminous). Three harvests of weed plants were accomplished, being six samples of 0,25 m² per plot. The identification of the species of the weed plants were carried out in the laboratory. The 55 weed species identified were distributed in 23 botanical families, being 43 of dicotyledonous species, 11 of monocotyledonous, and one of pteridophyta. The families Poaceae (monocotyledonous) and Asteraceae (dicotyledonous) were the most frequent and with large number of individuals. The most frequent species and with large number of plants per m² were Paspalum conjugatum P.J. Bergius (area A) and Homolepis aturensis (Kunth) Chase (area B) of the Poaceae family; Ageratum conyzoides L. of the Asteraceae family, presented the largest density. The similarity coefficients varied among the areas studied, being the largest indexes observed in the treatments that received fertilizers with organic matter (NPK+OM), particularly in the system cassava+fruit trees. The agricultural practices and the soil and crops management systems, had a great influence to the flora composition and in the weed plants communities size in each local area. The number of monocotyledonous was smaller in the treatment with NPK+OM than in the other treatments.
Weedy plants in agroforestry systems with cupuassu in the municipality of Presidente Figueiredo (Amazonas, Brazil)
Keywords: Theobroma Grandiflorum; Weeds; Monocotyledonous; Dicotyledonous; Theobroma Grandiflorum; Plantas Daninhas; Monocotiledôneas; Dicotiledôneas